1985
DOI: 10.1007/bf00249940
|View full text |Cite
|
Sign up to set email alerts
|

Marine microalgae as a potential source of single cell protein (SCP)

Abstract: The marine microalgae Tetraselmis suecica, Isochrysis galbana, Dunaliella tertiolecta and Chlorella stigmatophora are good biological sources of single cell protein (SCP). Protein content accounts for 39.12%-54.20% of the dry matter, D.tertiolecta having the highest. Lysine values are between 3.67 and 4.52 g/100 g of protein, and thus are higher than those for freshwater species. The total nucleic acid content is less than 7% of the dry matter; this value is definitely lower than that for yeasts or bacteria, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…These include: production of pigments such as phycocyanin, E-carotene, astaxanthin, chlorophyll-a and others (Tel-Or et al, 1980;Francis, 1987); polyunsaturated fatty acids such as y-linolenic acid, GLA (Grattan Roughan, 1989); enzymes such as ferredoxin (Tel-Or et al, 1980). It has also been suggested as a source of single cell protein (Fabregas & Herrero, 1985) or as aquaculture feed; however, because of the relatively high production costs, these latter applications seem improbable in the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%
“…These include: production of pigments such as phycocyanin, E-carotene, astaxanthin, chlorophyll-a and others (Tel-Or et al, 1980;Francis, 1987); polyunsaturated fatty acids such as y-linolenic acid, GLA (Grattan Roughan, 1989); enzymes such as ferredoxin (Tel-Or et al, 1980). It has also been suggested as a source of single cell protein (Fabregas & Herrero, 1985) or as aquaculture feed; however, because of the relatively high production costs, these latter applications seem improbable in the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 concentrating mechanism can enhance CO 2 supply to the RUBISCO pathway and increase the efficiency of nutrient utilization (Beardall and Giordano 2002). For industrial and aquacultural applications, D. tertiolecta is used to produce glycerol and the carotenoid β‐carotene (Ben‐Amotz and Avron 1980) and also used as a source of single‐cell protein and of minerals in fish diets and aquacultural feeding of marine fishes and bivalve mollusks (Fabregas and Herrero 1985, 1986). In addition, D. tertiolecta can be used in bioremediation for removing heavy metals from the environment because it synthesizes heavy metal binding peptides, phytochelatins, which play an important role in detoxification and accumulation of heavy metals (Hirata et al 2001, Tsuji et al 2002).…”
mentioning
confidence: 99%
“…In the context of raw materials there is distinguished between carbohydrates, lignins, lipids, proteins and special substances like dyes. The results of a brief literature study clearly showed that any kind of these raw materials can be extracted from micro algae, anyway [2,3,4,5,6,7]. and of total biomass 0.5 g · l -1 · d -1 , referred to the physiological state and the cultivation conditions.…”
Section: Algae Biomassmentioning
confidence: 99%